Analysis of Farmers' Income in The Integrated Cattle and Oil Palm Farming System in Labuhan Batu Regency - Suhendri, Suhendri; Purjianto, Purjianto; Febrianto, Eka Bobby (Jurnal Bisnis Tani, 2025)
The aim of this study is to analyze the economic contribution of oil palm and cattle farming and to evaluate the potential benefits of integrating these two systems for smallholder farmers in Labuhan Batu Regency. This research employs a field observation method using questionnaires and interviews, involving 34 respondents who are both oil palm farmers and cattle breeders. The study applies descriptive quantitative analysis to assess farmers’ production costs, revenues, and incomes. The results show that oil palm farming serves as the primary source of income, generating an annual net income of Rp 1,227,107,960, while cattle farming provides Rp 460,843,461. Integration of cattle and oil palm farming reduces production costs through the use of oil palm by-products as cattle feed and organic fertilizer, and improves land-use efficiency. The integrated system also adds value by producing biogas and reducing weeding costs. This study contributes to the existing literature by providing empirical data on the economic performance of integrated oil palm-cattle farming at the smallholder level in Labuhan Batu Regency, a topic that has been scarcely explored. The findings highlight that integrated farming can significantly enhance farmer income and support sustainable agricultural practices. It is recommended that smallholders adopt integrated systems more widely to realize these benefits, and that agricultural policies and extension services provide training and develop scalable models to support implementation.